Effects of artificial intelligence-based technologies implementation on the skills needed in the automotive industry a bibliometric analysis - Raluca Florentina Crețu; Daniela Țuțui; Viorel-Costin Banta; Elena Claudia Șerban; Laura-Eugenia-Lavinia Barna; Romeo-Cătălin Crețu (Amfiteatru Economic, 2024)
The development of emerging technologies, including artificial intelligence, has a significant effect on the automation of business processes related to the automotive industry, directly impacting employees skills and work tasks. The objectives of the study are: to identify the state of current research in the field of economics on the use of technologies based on artificial intelligence and the effects on employees competencies, to reveal the main themes addressed in the literature corresponding to the topic under investigation and to highlight a practical solution to assess employees required competencies in the automotive industry. The authors used bibliometric analysis to map the literature to highlight the effects of implementing AI-based technologies on the skills needed in the automotive industry. The sample selected from the Web of Science database consists of 866 papers published between 2018 and 2024 in the field of economics. The research results are obtained by analysing the intellectual and conceptual structure of the scientific production on the chosen topic and highlighting a practical solution related to the strategy of implementing artificial intelligence in an automotive industry company correlated with tasks design. This can be used to assess employees skills in the context of automating production processes, which gives it originality through an innovative, practice-oriented research approach and relevance to business decision-makers.
Keywords: C80; C88; D29; E23; L62; M11; 330; artificial intelligence (AI); skills; automotive industry; bibliometric analysis; automation; implementation; tasks